2010
DOI: 10.1038/oby.2009.441
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Multimers and ADIPOQ T45G in Coronary Artery Disease in Caribbean Type 2 Diabetic Subjects of African Descent

Abstract: Ethnic differences may affect the association of adiponectin (Ad) multimers with coronary artery disease (CAD). We analyzed the associations of total Ad, Ad multimers, and T45G polymorphism of ADIPOQ gene with pre‐existing CAD. We carried out a cross‐sectional study of 216 Afro‐Caribbean type 2 diabetic (T2D) subjects. Levels of total Ad, high molecular weight (HMW), middle molecular weight (MMW), and low molecular weight (LMW) isoforms were measured. Subjects were genotyped. Of the subjects studied, 57 had pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Numerous studies described significant negative correlations between adiponectin and the parameters of obesity. Low adiponectin concentrations which has been previously associated with coronary artery disease in the adult population of Guadeloupe [ 28 ] correlated with high plasma insulin levels and adverse blood lipid profile in the present study in children. Lower adiponectin levels in obesity were also associated with chronic inflammation, endothelial dysfunction, and insulin resistance [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 71%
“…Numerous studies described significant negative correlations between adiponectin and the parameters of obesity. Low adiponectin concentrations which has been previously associated with coronary artery disease in the adult population of Guadeloupe [ 28 ] correlated with high plasma insulin levels and adverse blood lipid profile in the present study in children. Lower adiponectin levels in obesity were also associated with chronic inflammation, endothelial dysfunction, and insulin resistance [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 71%
“…Foucan L. et al . (2010) showed that in Afro-Caribbean patients with type 2 diabetes, rs2241766 was associated with CAD under a dominant model [ 18 ]. A meta-analysis showed that the associations between rs266729 , rs2241766 and rs1501299 (+276G > T) in the ADIPOQ and CVD were significant but weak.…”
Section: Adiponectin-encoding Gene ( Adipoq )mentioning
confidence: 99%
“…Association studies between ADIPOQ SNPs and CAD also provided inconsistent results, but a recent meta‐analysis showed that the associations between rs2241766 (+45T>G) and rs1501299 (+276G>T) in the ADIPOQ gene and cardiovascular disease were significant but weak, and that studies are still required to confirm these associations. In our previous study in Afro–Caribbean patients with type 2 diabetes, rs2241766 was associated with CAD under a dominant model, as in Caucasian patients. Studies on rs17300539 (−11391G>A) and rs182052 (−10069G>A) are scarce, particularly in type 2 diabetes mellitus patients and in individuals of African descent.…”
Section: Introductionmentioning
confidence: 95%
“…Inconsistent results have been reported on the association between adiponectin concentrations and coronary artery disease (CAD), especially when the multimeric forms were evaluated. Thus, in a recent report, total Ad and LMW levels were not associated with myocardial infarction in non‐diabetic men, whereas the MMW:HMW ratio correlated with incident myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%